QUBIC: an algorithm for detecting cosmic rays - Ferazzoli, Sofia; Battistelli, Elia Stefano; Masi, Silvia; Barbavara, E.; Coppolecchia, A.; Costanza, B.; De Bernardis, P.; De Gasperis, G.; Gervasi, M.; Hamilton, J.-Ch.; Miron Granese, N.; Isopi, G.; et al. (Frontiers in Astronomy and Space Sciences, 2026)
IntroductionQUBIC (the Q & U Bolometric Interferometer for Cosmology) is an international ground-based experiment designed to observe the polarization of the cosmic microwave background. It has been installed at a high-altitude site in Alto Chorrillos, Argentina (4,869 m above sea level). At this altitude, the cosmic ray flux is high, thus requiring an advanced algorithm for their detection and removal from raw data. Cosmic rays can leave two types of traces in the data: above and below the noise level. This article describes an algorithm for detecting the above-noise traces.MethodsAn algorithm was developed for detecting cosmic ray events in the time-ordered data (TOD) of transition-edge sensor detectors (TES bolometers). Raw signals were pre-processed to obtain de-noised data. Events were searched by applying a threshold to isolate segments showing a rapid increase and subsequent exponential decay. The final goal is to fit each segment to extract the time scale of the candidate and verify the fit quality statistically.ResultsThe cosmic ray detection algorithm was applied to datasets acquired in Salta (Argentina) in 2022, during a testing campaign. So far, no candidates have been found after exploring different thresholds for initiating the cosmic ray search, along with various combinations of minimum points required for the sudden increase and exponential decay expected in the signal.DiscussionWe select only high signal-to-noise regions to find the most energetic cosmic ray candidates matching the filters proposed in the method. The null result is not surprising since, for the energy range of cosmic muons of interest here (approximately [1,100] Gev), the expected energy deposited in our very thin bolometer membranes is small and produces a small signal with respect to the measured noise. However, this methodology could be applied to future longer campaigns to estimate, from the largest (and rare) cosmic ray energy depositions, the TES time constants.